Audit of Crowns and Fixed Partial Dentures in a Nigerian Teaching Hospital (2017)
Aim: The purpose of this investigation was to document the reasons for placement, and replacement of crowns and fixed partial denture in a Nigerian Teaching Hospital. Methods: a retrospective review of patients that had advanced conservative procedures. A data collection form was used to gather the relevant information from the patients’ case notes. Section A sought information on age , gender, educational level, patients’ occupation etc. Section B recorded information on tooth/teeth involved, reason for fabrication of prosthesis and material used. Results: Three hundred and twenty six had 398 crowns while 23 patients received bridges. Patients’ ages ranged from 16-85 years with a mean of 47.7 ± 17.2 years and a male to female ratio of 1:1.3. Thirty five percent of the crowned teeth were in the upper right quadrant, followed by the upper left quadrant with 29.4%. Upper right central incisors were the most frequently (15.6%) crowned teeth. Endodontics and esthetics were the most common reasons for initial crown placement and replacement respectively. About 60% of bridges fabricated were new, while 22.2% of replaced bridges were due to fracture of porcelain and unacceptable marginal adaptation. Conclusion: Endodontics and esthetics were the most common reasons for initial crown placement and replacement